Monetising social media account / Nor Azizah Talkis - Talkis, Nor Azizah (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2018)
Students are typically easy to recognize social media influ-encers. Acknowledging this fact, on May 4, 2008, Building Department of Faculty of Architecture, Planning and Surveying (FSPU) has invited renowned local video makers, Sterk Production to talk in front of 550 students about how social media has changed their lives since seven years ago. Comprising of sev-en young gentlemen of mutual interest and talent, Sterk Production has never looked back since.